ChemInform Abstract: Cu‐Catalyzed Asymmetric Addition of sp2‐Hybridized Zirconium Nucleophiles to Racemic Allyl Bromides. Issue 30 (July 2015) - Sidera, Mireia; Fletcher, Stephen P.
Abstract Alkenylzirconium nucleophiles generated in situ by the hydrozirconation of terminal alkynes undergo dynamic kinetic asymmetric allylic alkenylation with racemic allyl bromides to give enantioenriched products.